The rhetoric of protest Philippine style - Casambre, Nelia G.
This study is undertaken to look into how Filipinos meets the crisis; how he uses words and strategies, as he asserts and describes himself in these movements. This study delimits itself to the rhetoric used after the Tarmac (August 21, 1983) up to December 1985. It will look into newspaper accounts of those events; it will include the researcher's experience with this reality and the feelings of the people she informally talked with.
Keywords: Rhetoric -- Political aspects -- Philippines -- History; Protest movements -- Political aspects -- Philippines -- History; Social movements -- Political aspects -- Philippines -- History